every hunter… - Константин Лидин; Елена Григорьева (Проект Байкал, 2022)
The color component of the urban environment is the most flexible and sensitive to changes. Of course, it is easier to repaint façades than to change the street pattern. Especially with the arsenal of tools offered by modern technologies. As lighting of streets and squares changes, facades also become variable, turning into gigantic screens before our eyes. Will we be able to keep the technological breakthrough within reasonable ethical and aesthetic limits? Experts from Sofia, Moscow and Smolensk are looking for answers to this question.